2018
DOI: 10.1136/bmj.k1591
|View full text |Cite
|
Sign up to set email alerts
|

Innovations to cut US healthcare prices

Abstract: Efforts to limit healthcare spending should focus on lowering prices as well as reducing use, argue Dhruv Khullar and Rahul Rajkumar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Further, in comparison to other countries, US consumers pay more for provider services, hospital services, drugs, and diagnostic tests [ 29 ]. In the US, the inpatient medication price is two times more than in Canada; MRIs cost three times more than in Australia, and the price for coronary artery bypass is four times more expensive than in the Netherlands (Figure 1 ) [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Further, in comparison to other countries, US consumers pay more for provider services, hospital services, drugs, and diagnostic tests [ 29 ]. In the US, the inpatient medication price is two times more than in Canada; MRIs cost three times more than in Australia, and the price for coronary artery bypass is four times more expensive than in the Netherlands (Figure 1 ) [ 30 ].…”
Section: Reviewmentioning
confidence: 99%
“…Cost is an important and growing concern in orthopedics and healthcare, as expenditures can dramatically outpace inflation and strain the healthcare system in an unsustainable way. [1][2][3] Therefore, it is imperative to evaluate orthopedic management strategies by not only their clinical benefits, but also their financial costs. A number of studies have identified substantial variation in the costs of implants and procedures-even between similar types of injurieswhich identifies a modifiable cost factor for improving value in orthopedic surgery.…”
Section: Introductionmentioning
confidence: 99%